1982
DOI: 10.1111/j.1699-0463.1982.tb00077_90a.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin in Experimental Granulation Tissue

Abstract: in experimental granulation tissue. Acta path. microbiol. immunol. scand. Sect. A. 90: 159-165. 1982.The temporal appearance of fibronectin in experimental granulation tissue has been studied using the immunoperoxidase technique on material fixed in formaldehyde, embedded in paraffin and pretreated with pepsin. Furthermore, the relationship between the distribution of fibronectin and connective tissue fibres, demonstrated as either argyrophilic or red by the van Gieson method, has been investigated. Fibronecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…It seems reasonable to assume that the first peak represents a 'spill-over' from plasma, which contains about 400 mg/l (Eriksen et al 1982). The second peak might represent a FN production by fibroblasts in the corneoscleral cicatrix, which would be in agreement with the findings of Holund et al (1982), who observed a maximum staining intensity for FN in experimental granulation tissue from day 6-10.…”
Section: Discussionsupporting
confidence: 91%
“…It seems reasonable to assume that the first peak represents a 'spill-over' from plasma, which contains about 400 mg/l (Eriksen et al 1982). The second peak might represent a FN production by fibroblasts in the corneoscleral cicatrix, which would be in agreement with the findings of Holund et al (1982), who observed a maximum staining intensity for FN in experimental granulation tissue from day 6-10.…”
Section: Discussionsupporting
confidence: 91%
“…The higher collagen content of wounds as assessed by the Haematoxylin and Eosin stain was better highlighted upon staining with Van Gieson. 28 Staining with Van Geison stain indicates staining of newly deposited collagen fibers in blue/green color. In addition, the alignment of the collagen fibers was also much better in wounds treated with the F1 and F2, also these were compact and parallel to the surface of the skin.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, functional weakness, reduced tensile strength and loss of tissue integrity may be a consequence of anti-Fn antibodies, and the anti-Fn antibodies may inhibit Fn from serving as a protein scaffold to direct tissue repair following inflammation. Although Fn is known to have an important role in wound healing, its role in parenchymal tissue injury is obscure [20], Anti-Fn antibodies have been shown to cause in vivo pathology using laboratory animals. Rabbits and mice immunized with Fn preparations developed glomerular injuries [21,22], and rats injected with anti-Fn antibodies developed glomerular injuries [23], Our preliminary results indicate an association between the occurrence of anti-Fn antibodies and active musculoskeletal involvement in SLE (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%